2019
DOI: 10.3171/2019.1.peds18232
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome of V-Y flap with latissimus dorsi and gluteal advancement for treatment of large thoracolumbar myelomeningocele defects: a comparative study

Abstract: OBJECTIVESurgical repair and closure of myelomeningocele (MMC) defects are important and vital, as the mortality rate is as high as 65%–70% in untreated patients. Closure of large MMC defects is challenging for pediatric neurosurgeons and plastic surgeons. The aim of the current study is to report the operative characteristics and outcome of a series of Iranian patients with large MMC defects utilizing the V-Y flap and with latissimus dorsi or gluteal muscle advanceme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Mortada et al 10 used the V–Y rotation advancement flap (butterfly flap) and found that the area that could be repaired was larger: one was located in the cervical region with a diameter of 8 cm, the other was located in the thoracolumbar region with a diameter of 16 cm, and the maximum width was more than 0.5 ratio to the back, accompanied with kyphosis. Masoudi et al 11 used V-Y flap with latissimus dorsi-treated large thoracolumbar MMC defects. This method is limited to latissimus flip flaps and muscle-skin grafts.…”
Section: Discussionmentioning
confidence: 99%
“…Mortada et al 10 used the V–Y rotation advancement flap (butterfly flap) and found that the area that could be repaired was larger: one was located in the cervical region with a diameter of 8 cm, the other was located in the thoracolumbar region with a diameter of 16 cm, and the maximum width was more than 0.5 ratio to the back, accompanied with kyphosis. Masoudi et al 11 used V-Y flap with latissimus dorsi-treated large thoracolumbar MMC defects. This method is limited to latissimus flip flaps and muscle-skin grafts.…”
Section: Discussionmentioning
confidence: 99%
“…Perinatal exposure to anticonvulsants, occupational exposure of the mother to radiation, heavy metals and certain chemical byproducts have been correlated with a higher risk of NTDs [13,14]. A previous population-based study in central Iran revealed that maternal history of abortion and maternal obesity were the only risk factors associated with NTDs in the Iranian population [15]. Although mandatory folic acid supplementation has been proposed in Iran since 2004, the incidence remains still high.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Early soft tissue coverage of the defect is imperative to support the repaired dura and neural placode to mitigate the risks of cerebral spinal fluid leak and infection. [8][9][10][11] When there is a paucity of soft tissue for primary coverage or subsequent wound breakdown, plastic surgeons are consulted for more complex wound closure. [12][13][14][15][16][17] More recently in the literature, perforator flaps have become a popular option for soft tissue closure.…”
mentioning
confidence: 99%
“…Multiple techniques have been described, including closure with or without paraspinal muscle turnover flaps, local regional flaps, perforator flaps, and regional muscle flaps 1–7 . Early soft tissue coverage of the defect is imperative to support the repaired dura and neural placode to mitigate the risks of cerebral spinal fluid leak and infection 8–11 . When there is a paucity of soft tissue for primary coverage or subsequent wound breakdown, plastic surgeons are consulted for more complex wound closure 12–17 …”
mentioning
confidence: 99%